Implications of trimethylamine N-oxide (TMAO) and Betaine in Human Health: Beyond Being Osmoprotective Compounds - Ilyas, Ashal; Wijayasinghe, Yasanandana Supunsiri; Khan, Ilyas; El Samaloty, Nourhan M.; Adnan, Mohd; Dar, Tanveer Ali; Poddar, Nitesh Kumar; Singh, Laishram R.; Sharma, Hemlata; Khan, Shahanavaj (Frontiers in Molecular Biosciences, 2022)
Osmolytes are naturally occurring small molecular weight organic molecules, which are accumulated in large amounts in all life forms to maintain the stability of cellular proteins and hence preserve their functions during adverse environmental conditions. Trimethylamine N-oxide (TMAO) and N,N,N-trimethylglycine (betaine) are methylamine osmolytes that have been extensively studied for their diverse roles in humans and have demonstrated opposing relations with human health. These osmolytes are obtained from food and synthesized endogenously using dietary constituents like choline and carnitine. Especially, gut microbiota plays a vital role in TMAO synthesis and contributes significantly to plasma TMAO levels. The elevated plasma TMAO has been reported to be correlated with the pathogenesis of numerous human diseases, including cardiovascular disease, heart failure, kidney diseases, metabolic syndrome, etc.; Hence, TMAO has been recognized as a novel biomarker for the detection/prediction of several human diseases. In contrast, betaine acts as a methyl donor in one-carbon metabolism, maintains cellular S-adenosylmethionine levels, and protects the cells from the harmful effects of increased plasma homocysteine. Betaine also demonstrates antioxidant and anti-inflammatory activities and has a promising therapeutic value in several human diseases, including homocystinuria and fatty liver disease. The present review examines the multifarious functions of TMAO and betaine with possible molecular mechanisms towards a better understanding of their emerging and diverging functions with probable implications in the prevention, diagnosis, and treatment of human diseases.